TRANSFORMASI HUKUM ISLAM DALAM SISTEM HUKUM NASIONAL: Idealisme dan Realitas - Siti Qomariyah (JURNAL PENELITIAN, 2014)
Development of Indonesian national law should not leave attention to development of legal plurality as its source. Focus of this study is to see the influence of Indonesian social factors on the development of Islamic law and how Islamic law can be integratively transformed into the National Law. By qualitative method and socio-legal approach and constructivism paradigm, this study bases on theories of social change influeces on Islamic law law without leaving methodology of usul fiqh and the sources of Islamic law. Islamic law has broad opportunity and experiences to be integratively transformed into national law within Indonesia's own character. Transformation can be done in the whole structure of Islamic law including its values of philosophy, principles and norms, and can be performed in all areas, both private and public Law, written law by political power and unwritten law with cultural approach. However, Islamic law as one of the Indonesia living laws and the sources of National law, still today is viewed in dichotomy to the National law and only transformed in limited norms. There are many obstacles to be transformed into national law integratively and widely, though Islamic law has wide space of interpretation and intellectualism that can adapt to different contexts and National law.